2017
DOI: 10.5489/cuaj.4143
|View full text |Cite
|
Sign up to set email alerts
|

Is computed tomography-defined obstruction a predictor of urological intervention in emergency department patients presenting with renal colic?

Abstract: Introduction: Our objective was to determine whether unilateral calculus-induced ureteric obstruction on computed tomography (CT) was independently associated with the need for urological intervention and 30-day return to the emergency department (ED). Methods:We performed a retrospective cohort study of patients with symptomatic urinary calculi diagnosed by unenhanced helical CT. Stepwise regression analysis was used to determine the predictors of urological intervention and 30-day return to the ED. Potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…A stone length >5 mm and upper ureteric stone location were significant risks for the need of intervention in most previous reports [ 5 , 7 , 11 ], as well as the present study. This can be explained by the natural history of ureteric calculi.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A stone length >5 mm and upper ureteric stone location were significant risks for the need of intervention in most previous reports [ 5 , 7 , 11 ], as well as the present study. This can be explained by the natural history of ureteric calculi.…”
Section: Discussionsupporting
confidence: 71%
“…Massaro et al [ 11 ] in 2017, evaluated predictors of urological intervention for CT-detected calculi causing ureteric obstruction. They had found that stone size, proximal ureteric location and severe pain (as indicated by higher opioid doses) were associated with the need for intervention within 30 days of presentation.…”
Section: Discussionmentioning
confidence: 99%
“…In a small Canadian retrospective series of 195 patients who presented with a ureteric calculus, 41% underwent intervention based on CT evidence of ureteric obstruction. 21 Stone size, a more proximal location and severe pain were associated with intervention but the degree of obstruction (a highly subjective measurement) did not influence management. Interestingly, none of the variables studied were predictive of readmission within 30 days.…”
Section: Discussionmentioning
confidence: 94%
“…In 9 studies, the urologic procedure rate varied from 6% (at 7 days) to 33% (at 30-60 days) (Table 9a and 9b in Supplement B). 22,23,24,59,[62][63][64][65][66][67][68][69][70] The only large population-level study showed a procedure rate of 13% in patients aged 18-64 years who were initially discharged from the ED. Stone size and location (as judged via CT), pain scores on discharge, and having private health insurance were found to be associated with a subsequent intervention in some studies.…”
Section: Summary Of Current Evidencementioning
confidence: 99%